The Role Of Demographic Factors On Students’ Online Self-Regulated Learning Strategies In Higher Education: Evidence From Indonesian University Students - Arrafii, Moh. Arsyad (International Journal of Linguistics and Indigenous Culture, 2026)
Self-Regulated Learning (SRL) is widely recognized as an important factor contributing to students’ academic success, particularly in online and technology-enhanced learning environments. This study examined the role of demographic factors in students’ use of SRL strategies in higher education. A quantitative survey design was employed involving 236 university students from public and private universities on Lombok Island, Indonesia. Data were collected using the Indonesian adaptation of the Online SRL Questionnaire (OSLQ). Independent-samples t-tests and one-way analyses of variance (ANOVA) were conducted to examine differences in SRL strategies based on gender, age group, field of specialization, and year level. The findings revealed no statistically significant differences in SRL strategies between male and female students, t(94.41) = 0.55, p = .587. Similarly, no significant differences were found across age groups, F(3, 232) = 2.36, p = .073, fields of specialization, F(4, 231) = 1.11, p = .352, or year levels, F(2, 233) = 2.63, p = .075. The effect sizes for all analyses were small, indicating that demographic characteristics explained little variation in students’ SRL strategies. The findings suggest that SRL may be influenced more by psychological, instructional, and environmental factors than by demographic characteristics. Implications for higher education practice and future research are discussed.